Macht oder ökonomisches Gesetz? Studien zur Entwicklung der ökonomischen Theorie XXXV - Trautwein, Hans-Michael (Schriften des Vereins für Socialpolitik, 2020)
»Political Control or Economic Law?« The volume at hand starts from Eugen von Böhm-Bawerk's famous 1914 piece on the limits of political influence on functional income distribution in the labour market. It contains essays on Böhm-Bawerk's temporal theory of capital and interest, partly in defence and adaptation to an environment of negative interest rates, partly in critical assessments. In the final essay Böhm-Bawerk's views on the relationship between political power and economic law are compared to those of Max Weber.